The Role of Human Resource Information Systems in Making Strategic Decisions (An Applied Study on the Iraqi Ministry of Finance) - Srour, Dr. Badia Abdellatif; Hammood, Mustafa Ibrahim (Research Parks Publishers, 2023)
This research aims to identify the role that human resources information systems play in improving strategic decisions and to explain the relationship of the impact of human resources information systems on improving strategic decisions. To achieve the objectives of the research, the impact between human resources information systems in its dimensions, which are (planning, recruitment, Compensation, training, performance evaluation) in improving strategic decisions. The methodology addressed a set of paragraphs, the most important of which is the research problem, the content of which is that there have been increasing interests and developments recently in human resources information systems. The research problem was defined in several questions centered around the form and nature of the relationship between the research variables, and in light of that, a hypothetical diagram was built that embodies the relationship. Among the variables concerned, a set of main and sub-hypotheses emerged from it. In order to achieve the aforementioned research goal and answer the research questions and test the validity of its hypotheses, the study relied mainly on (the questionnaire), which is the main tool for collecting data and information, and by adopting the descriptive approach. Because of that, a sample was chosen from the study population, so the research community was represented by all employees of the Iraqi Services Company. Banking, 400 questionnaires were distributed, of which 344 questionnaires were returned valid for analysis. After evaluating and testing the credibility and stability of the research measurement tools, data analysis and hypothesis testing were conducted using advanced statistical tools and analysis using statistical programs (SPSS. Ver. 25). The results showed the validity of the study hypothesis, and based on it, a number of conclusions were formulated.